1998
DOI: 10.1063/1.477276
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced reactions of methyl radical in solid parahydrogen

Abstract: Photolysis of methyl iodide in solid parahydrogen (p-H2) at about 5 K is studied with ultraviolet light at 253.7 and 184.9 nm. It is found that the light at 253.7 nm produces only methyl radical, whereas the light at 184.9 nm yields both methyl radical and methane. The mechanism of the formation of the photoproducts is elucidated by analyzing the temporal behavior of the observed vibrational absorption. It is concluded that methyl radical in the ground state does not react with p-H2 molecules appreciably but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…12,13,[15][16][17][18]21,22 The feasibility of the study of in-situ photolysis stems from the fact that molecules in solid p-H 2 happen to be free from the cage effect, which allows us to study photolytically produced fragments such as radicals originating from the parent molecule. 9,14,[23][24][25][26] In a previous paper we have observed Fourier transform infrared ͑FTIR͒ spectra of the CD 3 radical trapped in solid p-H 2 crystal. 9 The decrease in the absorption intensity of CD 3 and the increase in the intensity of CD 3 H were observed over a span of about one week at 5 K. As a result of that study, it was found that CD 3 reacts with surrounding hydrogen molecules through tunneling as follows:…”
Section: Introductionmentioning
confidence: 98%
“…12,13,[15][16][17][18]21,22 The feasibility of the study of in-situ photolysis stems from the fact that molecules in solid p-H 2 happen to be free from the cage effect, which allows us to study photolytically produced fragments such as radicals originating from the parent molecule. 9,14,[23][24][25][26] In a previous paper we have observed Fourier transform infrared ͑FTIR͒ spectra of the CD 3 radical trapped in solid p-H 2 crystal. 9 The decrease in the absorption intensity of CD 3 and the increase in the intensity of CD 3 H were observed over a span of about one week at 5 K. As a result of that study, it was found that CD 3 reacts with surrounding hydrogen molecules through tunneling as follows:…”
Section: Introductionmentioning
confidence: 98%
“…For conventional inert-gas matrices, however, the matrix cage effects typically prevent formation of free radicals from the photolysis of chloro compounds in situ because the Cl atom cannot escape from the original cage. 20 The diminished cage effect of the quantum solid p-H 2 as a matrix host has been demonstrated to allow the production of free radicals via photofragmentation [21][22][23][24] or bimolecular reactions [25][26][27][28][29] upon UV irradiation. For example, in our laboratory, irradiation with a mercury lamp at 254 nm of a p-H 2 matrix containing CH 3 I and SO 2 at 3.2 K followed by annealing of the matrix produced prominent features at 633.8, 917.5, 1071.1, 1272.5, and 1416.0 cm −1 that are attributable to ν 11 (C−S stretching), ν 10 (CH 3 wagging), ν 8 (SO 2 symmetric stretching), ν 7 (SO 2 antisymmetric stretching), and ν 4 (CH 2 scissoring) modes of CH 3 SO 2 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…41 In spectra recorded with p-H 2 as a matrix host, the line widths of guest molecules are narrow, 42,43 and small molecules might rotate in three dimensions 44,45 or along a single axis, 46 or maintain only internal rotation ͑torsion͒. 48,49 Raston and Anderson 50 photodissociated Cl 2 trapped in solid p-H 2 with laser light at 355 nm and produced isolated Cl atoms; a direct absorption line at 943.8 cm −1 associated with the spin-orbit transition 2 P 1/2 ← 2 P 3/2 of atomic chlorine was observed. One might readily produce radicals by UV irradiation in situ of a p-H 2 matrix containing suitable precursors, as previously demonstrated with formation of CH 3 and C 2 H 5 , respectively, from photolysis of CH 3 I and C 2 H 5 I isolated in solid p-H 2 .…”
Section: Introductionmentioning
confidence: 99%